Dossier : the Association of Caribbean States - Altmann B., Josette (FLACSO General Secretariat San JoséCR, 2007)
Provides a brief historical review of the ACS timeline. Deals with the organisational structure and areas of activity of the ACS. Highlights some challenges facing the organization.